A phenomenological model for predicting long-term high temperature creep life of materials from short-term high temperature creep test data. (15th July 2021) - Ayubali, Arsath Abbasali; Singh, Alok; Shanmugavel, Balasivanandha Prabu; Padmanabhan, K.A.
Highlights: Power law creep, with stress exponent, n, f ( T, grain size ), predicts long-term creep life of critical industrial components. Model parameters calculated using just short-term creep test results are sufficient to predict long-term creep life accurately. Accuracy of predictions is vastly improved by using suitable material-dependent weighting factors. The prediction accuracy of the new model is superior to those of traditional TTP methods that have held sway since 1960's. An industry-oriented creep degradation analysis results in real-time warning stages according to a pre-selected criterion. Abstract: A phenomenological analysis for predicting the long-term creep life of high temperature materials at different temperatures using model parameters derived from short-term creep tests is presented. The model invokes Maxwell-Boltzmann temperature dependence, as rigorously developed in a recent analysis pertaining to the power law domain and a modified form of the Monkman-Grant hypothesis for isothermal conditions. In addition, the model provides, by pattern recognition, suitable weighting factors for the role of strain rate and temperature. The result is a material-dependent analysis which uses only short-term creep test data but is able to predict accurately both the short- and long-term creep behaviour of several complex creep-resistant alloys. This analysis is validated using reliable and accurate creep data taken from NIMS (National Institute of Materials Science, Japan) database pertaining to 10 industrial, high temperature alloys. The consistency or otherwise of the predictions is examined and the importance of the weighting factors in ensuring accurate predictions is emphasized. Graphical abstract: Image, graphical abstract